Lateral Thinking Practice on ELT Situation: Innovative Strategy to Promote HOTs - Putu Yoga Sathya Pratama; Ni Nyoman Padmadewi; I Gusti Ayu Lokita Purnamika Utami (Universitas Muhammadiyah Metro, 2022)
Several conceptions of convergent and divergent thinking are being compared to determine the superior one. However, lateral thinking has emerged, blending convergent and divergent thinking whose potentials impact High Order Thinking Skills (HOTS). This conceptual writing aimed to describe the practice of lateral thinking skills in ELT situations. Furthermore, its role in promoting HOTS was discussed, especially in modern classrooms. A library research design was used to gather primary data through literature reviews. The examinations were done qualitatively; triangulated for more reliability and compelling. The findings reveal that lateral thinking is most commonly delivered on a problem-based learning model, which might be utilized to encourage students to think beyond the box in the future. Lateral thinking is also adaptable and applicable in various settings and courses. It is anticipated that practicing lateral thinking in the modern classroom would significantly impact students' problem-solving skills, discover new solutions, create discoveries and breakthroughs. It is highly suggested that both teachers and students employ lateral thinking to ensure that HOTS is trained to its full potential.